Change management through strategic leadership: the mediating effect of knowledge management in public organizations, Ethiopia - Worku Lemlemu Ferede; Yalew Endawoke; Gedif Tessema (Future Business Journal)
Abstract The purpose of this study is to investigate the effects of strategic leadership on change management within public organizations, mediated by knowledge management. In this study, an explanatory design and a quantitative approach were employed. A structured questionnaire survey was administered to 366 randomly selected respondents from public organizations in northwest Ethiopia. The reliability and validity of the scale items were rigorously assessed, and the data were analyzed using partial least squares structural equation modeling. The findings reveal the direct effects of strategic leadership and knowledge management on change management, with knowledge management partially mediating the relationship between strategic leadership and change management. The study addresses a significant gap in the literature by shedding light on how strategic leadership drives change in public organizations. Its interdisciplinary approach and examination of mediation offer original insights, paving the way for future studies on challenges within public service contexts. Recommendations underscore the importance of considering local context, embracing adaptive leadership, and integrating knowledge processes for effective change management in public organizations.